علاقة الميول المهنية بمستوى الطموح لدى طلبة سنة ثالثة ليسانس لقسم العلوم الاجتماعية - منصر، كريمة (جامعة الوادي university of Eloued, 2019)
تهدف الدراسة إلى معرفة العلاقة بين الميول المهنية ومستوى الطموح لدى طلبة سنة ثالثة ليسانس لقسم العلوم الاجتماعية بجامعة الشهيد حمه لخضر بالوادي وقد جاءت اشكالية الدراسة كما يلي : هل توجد علاقة بين الميول المهنية ومستوى الطموح لدى طلبة سنة ثالثة لقسم العلوم الاجتماعية ؟ ليتفرع التساؤل العام إلى عدة أسئلة جزئية . وقد تم استخدام المنهج السببي المقارن الملائم لطبيعة الدراسة الحالية ، وقد اختيرت العينة بالطريقة العرضية المتمثلة في مجموعة من الطلبة والطالبات من قسم سنة ثالثة علوم إجتماعية بجامعة الشهيد حمه لخضر، أما فيما يتعلق بأداة الدراسة فكانت عبارة عن مقياسين الأول يقيس الميول المهنية مكون من 29 بند والثاني مستوى الطموح ويحوي على 27 بند، وبعد التأكد من الخصائص السيكومترية للأداة ومدى قياسها للغرض الذي وضعت لأجله وذلك بحساب صدقه وثباته ، طبقت على عينة مكونة من 152طالب وطالبة معتمدين على الأساليب الاحصائية التالية في معالجة البيانات المتحصل عليها المتمثلة في : المتوسطات الحسابية والانحراف المعياري واختبار تا للدلالة بين الفروق . وتم من خلالها التوصل الى النتائج التالية : لا توجد فروق ذات دلالة إحصائية في الميول المهنية لدى طلبة سنة ثالثة لقسم العلوم الاجتماعية تعزى لمتغير الجنس . لا توجد فروق ذات دلالة إحصائية في مستوى الطموح لدى طلبة سنة ثالثة لقسم العلوم الاجتماعية تعزى لمتغير الجنس . لا توجد فروق ذات دلالة إحصائية في الميول المهنية لدى طلبة سنة ثالثة لقسم العلوم الاجتماعية تعزى لمتغير التخصص . لا توجد فروق ذات دلالة إحصائية في مستوى الطموح لدى طلبة سنة ثالثة لقسم العلوم الاجتماعية تعزى لمتغير التخصص . لنستنج في الأخير أنه لا توجد علاقة بين الميول المهنية ومستوى الطموح لدى طلبة سنة ثالثة لقسم العلوم الاجتماعية حسب الدراسة الحالية . وقد تم عرض وتحليل ومناقشة و تفسير النتائج في ضوء الجانب النظري بالإضافة الى الواقع الميداني والدراسات السابقة . Summary The study aims at finding out the relationship between the professional orientation and the level of ambition among third year students, a bachelor's degree for the social sciences department at the University of Shaheed Hama Lakhdar in Wadi. The problem of the study came as follows: Is there a relationship between professional orientation and level of ambition among third year students of the Department of Social Sciences? The general question is divided into several partial questions. The sample was used by a group of male and female students from the third year of social sciences at the University of Martyr Hama Lakhdar. In terms of the study tool, the first measure was to measure the professional orientation of 29 items And the second level of ambition and contains 27 items, and after ascertaining the characteristics of the instrument and the extent of measurement of the purpose for which it was established by calculating the validity and stability, applied to a sample of 152 students, relying on the following statistical methods in processing data obtained Altmth In: arithmetical averages, standard deviation, and t-test to indicate differences. The following results were obtained: There were no statistically significant differences in the professional attitudes of the third year students of the social sciences department due to gender variable. There were no statistically significant differences in the level of ambition among third year students of the social sciences department due to gender variable. There were no statistically significant differences in the professional orientation of third year students of the social sciences department due to the specialization variable. There were no statistically significant differences in the level of ambition among third year students of the Department of Social Sciences due to the variable of specialization. Lesteng concluded that there is no relationship between professional orientation and level of ambition among third year students of the Department of Social Sciences according to the current study. The results were presented, analyzed, discussed and interpreted in light of the theoretical side as well as the field reality and previous studies.
دراسة ميدانية في كلية العلوم الإجتماعية والانسانية جامعة الشهيد حمة لخضر الوادي
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: الميول المهنية، مستوى الطموح; Penchants professionnels, niveau d'ambition; Professional inclinations, level of ambition